Предмет вожделения № 1: роман / А. В. Литвинова, С. В. Литвинов - Литвинова Анна Витальевна (Русский стиль, 2004)
Экземпляры: ф.1 (20160422) / Инвентарный номер: 35849 / Цена: 59.00 / Авт.знак: Л 64 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6